Ответ:
Пошаговое объяснение:
3(8x - 6) = 4(6x - 4,5)
24x - 18 = 24x - 18
24x - 24x = 18 - 18
0 = 0
x є (-∞ ; ∞)
уравнение имеет множество решений
===================
3(5x - 7) = 5(3x + 4)
15x - 21 = 15x + 20
15x - 15x = 20 + 21
0 ≠ 41
нет решений
=====================
6(2x + 1/6) = 5(2,4x + 0,2)
12x + 1 = 12x + 1
12x - 12x = 1 - 1
================
2(9x + 3) = 3(1 + 6x)
18x + 6 = 3 + 18x
18x - 18x = 3 - 6
0 ≠ -3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
3(8x - 6) = 4(6x - 4,5)
24x - 18 = 24x - 18
24x - 24x = 18 - 18
0 = 0
x є (-∞ ; ∞)
уравнение имеет множество решений
===================
3(5x - 7) = 5(3x + 4)
15x - 21 = 15x + 20
15x - 15x = 20 + 21
0 ≠ 41
нет решений
=====================
6(2x + 1/6) = 5(2,4x + 0,2)
12x + 1 = 12x + 1
12x - 12x = 1 - 1
0 = 0
x є (-∞ ; ∞)
уравнение имеет множество решений
================
2(9x + 3) = 3(1 + 6x)
18x + 6 = 3 + 18x
18x - 18x = 3 - 6
0 ≠ -3
нет решений
=====================